Heat Capacities and Thermodynamic Functions of New Cobalt Manganites LaM2IICoMnO6 (MII—Mg, Ca, Sr, Ba) in the 298.15–673 K Temperature Range - Kasenov, B.K.; Turtubaeva, M.O.; Amerkhanova, Sh.K.; Kasenova, Sh.B.; Sagintaeva, Zh.I.; Kuanyshbekov, E.E.; Seisenova, A.A.; Smagulova, D.I. (Pleiades Publishing, 2015)
Temperature dependences of the heat capacities of cobalt manganites LaM2 CoMnO6 (MII = Mg,Ca, Sr, Ba) are investigated by means of dynamic calorimetry in the temperature range of 298.15–673 K. It is established that cobalt manganites display λ-like effects on the °Cf( curve, which are likely to be related to the type II phase transitions. Equations for the temperature dependence of the heat capacity of cobalt man-ganites are derived from the experimental data with allowance for phase transition temperatures. The values of Cp (T) and thermodynamic functions Н°(Т) – Н°(298.15), S°(T), and Фхх(Т) are calculated.
Keywords: cobalt manganite; dynamic calorimetry; heat capacity; thermodynamic functions